Does the Carhart (1997) Four-Factor Model Still Applicable? Evidence from Stocks Listed on Bursa Malaysia - Rohuma, Hani Nuri; Alzwi , Asma S. (International Journal of Economics and Financial Issues, 2025)
Researchers and investors frequently use different financial models to explain stock returns. These models’ applicability for evaluating various stock price anomalies is investigated across several markets. This research examines Carhart’s (1997) four-factor model in Bursa Malaysia on four portfolios constructed according to their market value from 1 January 2011 to 1 January 2021. The results of the Robust Standard Errors and Ordinary least squares (OLS) regressions emphasised that the Carhart (1997) four-factor model has a strong return explanatory power in Bursa Malaysia. However, the results also asserted that the momentum effect does not exist in the four-sized portfolios in Bursa Malaysia.